Streptozotocin increases free fatty acids and decreases phospholipids in rat brain - Müller, Dirk; Nitsch, Roger M.; Wurtman, Richard J.; Hoyer, Siegfried (Journal of neural transmission, 1998)
Streptozotocin (STZ) is a diabetogenic drug that disrupts glucose and energy metabolism in brain. To study its effect on brain lipids, tissue concentrations of free fatty acids and phospholipids were measured in the temporal cortex and the hippocampus of adult rats 3 weeks after a single intracerebroventricular (icv) injection of STZ. STZ increased concentrations of palmitic acid and stearic acid in temporal cortex and these of arachidonic acid both in the anterior part of the hippocampus and in CA1. In addition, palmitic acid and stearic acid concentrations were elevated in the anterior hippocampus. In contrast, STZ decreased brain cortex levels of phosphatidylethanolamine and phosphatidylserine. These data show that STZ alters brain lipid metabolism. They suggest that oxidative phospholipid breakdown is accelerated by STZ. These changes may be related to decreased brain glucose utilization and energy formation.